The Existence of 'Urf as a Source of Law: A Comparative Study of Madzhab Four's Thought on Local Traditions in Indramayu - Syukron Makmun; Sugiarti; Ahmad Basuni; Indah Nurhaliza; Ahkmad Fathus Sidik (STAI Al-Mas'udiyah, 2025)
This article examines the existence of 'urf (custom) as a source of Islamic law within the framework of the four major legal schools (madzhab), namely Hanafi, Maliki, Shafi'i, and Hanbali, and its application to local traditions in Indramayu, West Java. Using a comparative qualitative methodology with a library research approach, this study analyzes the epistemological foundations, scope, and conditions for the acceptance of 'urf in each madzhab and then contextualizes those criteria against selected Indramayu traditions, including ngunjung (ancestral grave visitation), sedekah bumi (earth almsgiving ceremony), ngarot (pre-harvest youth ritual), mapag sri (rice-welcoming procession), and tahlilan (communal Quranic recitation for the deceased). The findings reveal that while each madzhab differs in the weight and conditions attributed to 'urf, all four schools fundamentally recognize valid custom as a legitimate auxiliary source of law. Maliki and Hanafi traditions grant 'urf the broadest operative role, whereas Shafi'i and Hanbali schools impose stricter conditions. When applied to Indramayu traditions, most practices are classifiable as 'urf shahih (valid custom) after appropriate purification of syncretic elements, making them legally permissible within a maqashid al-shari'ah framework.